Are Portuguese Higher Education Students Motivated to Study English as a Second/Foreign Language? - Bessa, Luciana Cabral P.; Silva, Elisabete Mendes; Meirinhos, Galvão; Silva, Rui (Theory and Practice of Second Language Acquisition, 2024)
Being motivated is fundamental for any individual to achieve personal and professional success. In the context of learning in Higher Education, Motivation is crucial for achieving this success. Understanding the motivational state of students is essential for higher education managers and teachers. Understanding students’ Amotivation, intrinsic and extrinsic motivation can provide vital information to initiate changes in teaching and learning. In this sense, measuring Amotivation, Intrinsic Motivation, and Extrinsic Motivation allows for understanding the general state of students’ Motivation. This study aims to analyze the Motivation of 145 Portuguese Higher Education Students (70 Male and 75 Female) aged between 17 and 47 years old who studied the second/foreign language (English) in Portugal during the Academic Year of 2020/2021. We used the Academic Motivation Scale to measure Motivation to study English. The results show that students are not demotivated. The Motivation that prevails in the results is Intrinsic Motivation, and Extrinsic Motivation was insignificant. This study’s results contribute to the literature on Motivation to study Second Language, especially concerning the need to understand why students are only intrinsically motivated. Are the lessons, the teaching methodologies, the techniques and the contents not able to motivate them?